From Capacitance-Controlled to Diffusion-Controlled Electrochromism in Nb-Doped TiO2 Nanocrystalline Electrodes. (7th July 2017) - Giannuzzi, Roberto; Da Silva, Rafael; Barawi, Mariam; De Trizio, Luca; Veramonti, G.; Qualtieri, A.; Manna, Liberato; Manca, Michele
Abstract : N-doped transition-metal oxides nanocrystals are interesting candidates as active materials for near-infrared-selective electrochromic devices due to their peculiar optoelectronic properties arising from their outer-d valence electrons. Among them, TiO2 is particularly attractive, as it can be conveniently modified by substitutional aliovalent doping, using, for example, Nb 5+ ions, to enhance electron conductivity and to induce the appearance of an intense surface plasmonic resonance in the near-infrared range. Four batches of Nb-doped TiO2 nanocrystals with different doping levels (from 0% to 15% of niobium content) have been here investigated and used as active electrodes in lab-scale electrochromic devices, capable of dynamically modulating the intensity of near-infrared radiation upon the application of a modest bias voltage. It has been then ascertained that an appropriate control of two fundamental electrochemical processes occurring at the interface with the electrolyte, namely the surface capacitive charging and Li + insertion, makes possible to selectively (and independently) regulate their optical features over the "near-infrared only" and the "visible + near-infrared" regimes, respectively.